2013
DOI: 10.30843/nzpp.2013.66.5621
|View full text |Cite
|
Sign up to set email alerts
|

The potential of ethyl formate carbon dioxide to control a range of horticultural pests

Abstract: Ethyl formate (EF) is a generally recognised as safe (GRAS) compound that can be applied as a fumigant to disinfest fresh produce This paper reports initial research to determine the dose responses of various pests to ethyl formatecarbon dioxide treatment during 1 2 3 and 4h treatments at ambient temperatures between 18 and 23C Thrips (mixtures of Thrips tabaci and Frankliniella occidentalis) on lupin flowers obscure mealybugs (Pseudococcus viburni) on potatoes and greedy scale (Hemiberlesia rapax) on potatoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…mites, mealybugs, thrips, scale insects and spiders), as their interception during phytosanitary inspection can result in 'rejection or fumigation' of capsicum consignments. A 1-hour 1-1.5% EF treatment has the potential to control other pests that are susceptible to EF treatment, such as some species of thrips and scale insects and mobile life stages of some mealybug and mite Griffin et al 2013;Jamieson et al 2014b, c).…”
Section: Discussionmentioning
confidence: 99%
“…mites, mealybugs, thrips, scale insects and spiders), as their interception during phytosanitary inspection can result in 'rejection or fumigation' of capsicum consignments. A 1-hour 1-1.5% EF treatment has the potential to control other pests that are susceptible to EF treatment, such as some species of thrips and scale insects and mobile life stages of some mealybug and mite Griffin et al 2013;Jamieson et al 2014b, c).…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 0.3% EF (+CO 2 ) treatment for 1 h has the potential to control 99% of onion thrips and latania scale, and 0.81% EF (+CO 2 ) treatment for 1 h has the potential to control obscure mealybug. Other studies have also shown that mealybugs, thrips and scale insects are susceptible to EF+CO 2 (De Lima 2009, 2010Chhagan et al 2013;Griffin et al 2013;Jamieson et al 2013) requiring concentrations of up to 1% EF (+CO 2 ) for 1-4 h to control these pests.…”
Section: Discussionmentioning
confidence: 99%
“…EF breaks down into formic acid and ethanol and is exempt from Maximum Residue Limits (MRL) for use as a postharvest treatment on plant products (MPI 2013). EF is effective against a range of pests on a range of commodities (Simpson et al 2004(Simpson et al , 2007van Epenhuijsen et al 2007;De Lima 2009, 2010Chhagan et al 2013;Griffin et al 2013;Jamieson et al 2013;Pupin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternatives to MB are being sought by the apple industry to ensure continued market access should MB be restricted, become uneconomical or become unavailable. Ethyl formate (EF) is a generally recognised as safe (GRAS) fumigant that is reported to control many pest species De Lima 2009, 2010Griffin et al 2013;Jamieson et al 2013Jamieson et al , 2014Jamieson et al , 2015Pupin et al 2013;Simpson et al 2004Simpson et al , 2007van Epenhuijsen et al 2007). It has the potential to be used in a management programme with no detectable residues.…”
Section: Introductionmentioning
confidence: 99%